The Heartside: The Visual Communication Design of Engaging with Young Women to Address Menstrual Taboos - Wang, Meilin (Auckland University of Technology, 2018)
Creating a positive narrative around menstruation has been the focus of my research. I have investigated how electronic stickers (e-stickers) can be used to create visual narratives that enable young women to communicate their menstrual experiences via chat on social media. Social, historical and cultural pressures impact the taboos that surround interpersonal communication related to menstruation; however, social media opens new avenues for young women to talk about having their period. During my research, I considered the ways that young women use visual and symbolic communication to convey personal and emotional information, particularly through using e-stickers, emojis and emoticons on their favourite social networking service (SNS) platforms. My research highlighted a lack of, and an opportunity to create, positive symbolic representation associated with menstruation for social media users. Employing an illustrative methodology, I have created a female character and prototyped a set of e-stickers that show her physical experiences and mood during the different phases of her menstrual cycle.
Keywords: e-Sticker; Menstrual taboos; Menstruation; Women; Visual communication